Measuring self-regulation after nutrition education modules with Self Determination Theory (SDT) intervention among teachers with or at Risk Metabolic Syndrome - Ridwan Mochtar Thaha; Nurzakiah Hasan; Veni Hadju; Nurhaedar Jafar; Syurawasti Muhiddin; Ida Leida Maria (Elsevier, 2021)
Objective: This study aims to measure changes in autonomy in groups that have been given nutrition education by applying the SDT concept. Methods: The non-randomized pre-post intervention study design involved 63 teachers in the intervention group and 60 teachers in the control group. Nutrition education by applying the SDT concept and measurement is carried out using the Treatment Self-Regulation Questionnaire (TRSQ). Results: The results showed that there was a significant change in support autonomy in the intervention group (p = 0.034) and not in the control group. Controlled variables and amotivation did not show significant differences in the two groups, but changes for the better occurred in the intervention group. Conclusion: The application of the SDT concept can increase support for autonomy. This is expected to support sustainable behavior change.